Prison ideas and architecture 1850-today: - Hedda Giertsen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article discusses the use of prisons as punishment in Norway during the period 1850 to today. It looks at ideas about prisons and how they manifest themselves in prison sites and buildings. It also investigates the implications of various prison ideas and designs to prisoners and prison policy. Parts of the article are based on an exhibition that took place in Oslo in 2018: Six Norwegian prisons 1850-today: Ideas, spaces, experiences. The exhibition included a total of 20 interviews in which prisoners were asked whether prison ideas and designs were relevant to them. The article ends with a discussion of the implications of architecture for prisons, their purposes, and their effects.